MULTI-DIMENSIONAL STUDY OF PROTECTED FOREST MANAGEMENT POLICY IN JANTHO DISTRICT, ACEH BESAR - Rivai Ahmad Ahmad; Teuku Muhammad Zulfikar; Badruzzaman; Zamzami (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
The complexity of protected forest management policy in Jantho Subdistrict, Aceh Besar, reveals a significant discrepancy between the de jure designation of the area by the government and the de facto land use by the community, which has been going on for generations. The main pressure on the Jantho Protected Forest has shifted from illegal logging to permanent illegal land occupation and land speculation practices along the Jantho–Lamno development project route. Although conservation efforts in the core conservation area (Jantho Nature Park, Jantho Pine Forest Reserve) showed an increase in management effectiveness based on the 2019 METT evaluation, external pressures in the buffer zone remain high. To resolve tenure conflicts and ensure sustainable conservation, management policy must adopt a multi- stakeholder approach. Strategic vertical collaboration is needed between the Aceh Besar District Government, the Aceh Provincial Government, and the Ministry of Environment and Forestry. These efforts must be supported by the preparation of a comprehensive integrated Academic Paper, in accordance with the DPRC's recommendations. The long-term solution lies in the implementation of the Social Forestry model, particularly Community Forests (CF) or Customary Forests, as a mechanism to legitimise community management rights while maintaining the essential conservation functions of forests. Taking advantage of the momentum of the discussion of the 2025-2029 MTDP Draft Qanun provides political legitimacy for the Aceh Besar Regency Government to fight for a road map for revising the status of this area.